Vida eclesial e meios de comunicação: uma análise da prática comunicacional na Igreja Católica a partir do decreto Inter Mirifica - Malaspina, Eduardo (2012)
Such an essay proposes an angle for reflection upon Catholic Church documents about ecclesiastic life and communication. The theme brings out a reflection moment from the Tridentin Period (Post-Reform and Against-Reform) and goes through the Conciliar period (Vatican II Ecclesial Council) and directly influences upon Latin American and Caribbean Church with CELAM documents about communication. Through a critical historic analysis based on interdisciplinary interaction main modern and post-modern cultural aspects could be pictured, and thus enlighten a smoother path which led to a better understanding on the existing disruption and continuity expressions before theological and ecclesiastic questionings in the scope of communication. Modern times and post-modernity both have caused enormous changes in people's way of thinking, acting and living, in social groups as well as in Church. In a fast changing world, communication ways also do change so rapidly and influence forming a rather complex global society. In the evangelization process, communication is surely a big concern, especially in the aspect of striving to look for means to keep providing people with the right feedback within such a challenging 'theological place' which is nowadays media society